Flexible, Free‐Standing and Holey Graphene Paper for High‐Power Supercapacitors. Issue 11 (26th September 2016) - Ferrero, Guillermo A.; Sevilla, Marta; Fuertes, Antonio B.
Abstract: Flexible supercapacitors based on bendable electrodes have aroused much interest for integration in clothing materials and portable electronic devices. However, simultaneous achievement of high areal energy and high power densities still presents a great challenge. Herein we report the fabrication of free‐standing, flexible graphene papers suitable for high‐performance flexible supercapacitors. The binder‐free graphene paper is made up of two types of holey graphene units (i.e., wrinkled graphene sheets and graphene nanoscrolls) that produce closely interconnected, porous 3D graphene architectures. The graphene papers reported here can be fabricated with a variety of thicknesses and areal densities, in the 10–70 μm and 1–5 mg cm −2 ranges, respectively. They exhibit a remarkable electrochemical performance in aqueous electrolytes: a) a high cell areal capacitance (230–190 mF cm −2 in H2 SO4 and 180–170 mF cm −2 in Li2 SO4 ), b) an outstanding capacitance retention of 60 % at ultra‐large current densities of 1200 mA cm −2, c) an excellent long‐term cycling stability and d) high areal power (≈280 mW cm −2 ) and energy densities (≈32 and ≈60 μWh cm −2 in H2 SO4 and Li2 SO4, respectively). These highly flexible graphene papers show a great improvement, in terms of areal energy‐power densities, in relation to the state‐of‐the‐art graphene‐based film electrodes. Abstract : Powerful paper : The fabrication of free‐standing, flexible graphene papers for high‐performance flexible supercapacitors is presented herein. The binder‐free graphene paper, made up of wrinkled graphene sheets and graphene nanoscrolls, can be fabricated with a variety of thicknesses and areal densities. The graphene‐based supercapacitor integrates both high areal energy and high power densities in aqueous electrolytes.